2011
DOI: 10.1136/bjsm.2010.078824
|View full text |Cite
|
Sign up to set email alerts
|

Injection treatments for patellar tendinopathy

Abstract: ObjectiveInjection treatments are increasingly used as treatment for patellar tendinopathy. The aim of this systematic review is to describe the different injection treatments, their rationales and the effectiveness of treating patellar tendinopathy.MethodsA computerised search of the Medline, Embase, CINAHL and Web of Knowledge databases was conducted on 1 May 2010 to identify studies on injection treatments for patellar tendinopathy.Results11 articles on seven different injection treatments (dry needling, au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 53 publications
3
35
0
3
Order By: Relevance
“…Kongsgaard et al 54 reported that steroid injection used in isolation was associated with a poorer outcome at 6 months compared with exercise. It must be emphasized that there are few high-quality studies on injection therapies to date, 88 and injections are often offered when rehabilitation has been inadequate. 80 The key strategy for avoiding multiple passive interventions is setting realistic goals based on a sound understanding of the condition and its rehabilitation.…”
Section: Inaccurate Beliefs and Expectations About Painmentioning
confidence: 99%
“…Kongsgaard et al 54 reported that steroid injection used in isolation was associated with a poorer outcome at 6 months compared with exercise. It must be emphasized that there are few high-quality studies on injection therapies to date, 88 and injections are often offered when rehabilitation has been inadequate. 80 The key strategy for avoiding multiple passive interventions is setting realistic goals based on a sound understanding of the condition and its rehabilitation.…”
Section: Inaccurate Beliefs and Expectations About Painmentioning
confidence: 99%
“…Two recent meta-analyses of different injection therapies for tendonopathy both concluded that all treatments had promising effects, with the exception of steroids, which often showed relapse of symptoms in the long term [11,43]. However, another conclusion might be that the other techniques are not necessarily beneficial, but that steroids are detrimental to tendons.…”
Section: Tendonosismentioning
confidence: 99%
“…7,10,16,[23][24][25]28,30,45 Evidence suggests that analgesic injection is not superior to DN in other regions of the body. 17,21,46 Therefore, it is possible that cortisone injection for GTPS is not superior to DN. If DN is equally or more effective in treating GTPS than cortisone injection, then effective patient care could be delivered without subjecting patients to the harmful effects of steroids.…”
Section: T T Conclusion: Cortisone Injections For Gtpsmentioning
confidence: 99%